Peran Perencanaan Pembelajaran Terhadap Kualitas Pengajaran - Sri Putrianingsih; Ali Muchasan; M Syarif (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
Education is an e effort to obtain important information that has never been received by students. The education that the theacher will convey to students should be well prepared and maximized. Through education delived by teachers to students can have an impacton increasing the creativity, talent, and intelligence of a students. The effect of the learning delivered by teacher affects the moral personality and intellectuals abilities of students, so there is a need for maximum planning before learning process is carried out, namely by doing lesson planning, before learning taker place. It can be a guide and support for the implementation of teaching so as to create good quality theaching.